Analisis Hubungan Eksekutif dan Legislatif dalam Pembuatan Perda APBD di Provinsi Sulawesi Barat - Megawati Megawati (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
This research aims to determine the planning, discussion, and determining process PERDA (local regulations) APBD (budget of income and expenditure) in the Province West Sulawesi and the factors that influence. The researh method used is research qualitative with parse the data is descriptive. The technique collection of the data by observation, interview, literature review, and docomentation by using technical analysis descriptive qualitative.The result of the reseacrh showed that planning, discussion and determining process in the making PERDA APBD in the Province West Sulawesi has followed the procedure of preparing APBD is there. But in the planning process PERDA APBD was not maximal. This is showed with returned of KUA (General Policy of Budget) PPAS (priority of the provisional budget ceiling) to the executive due to contraints such as institutional changes in the government of west sulawesi and deos not correspond with the initial draft. This makes discussion proccess tends slow and dynamic. While determining proccess is done on time. In the proccess involving executive and legislative, but in the relations between them does not look to good.